Insights into the mechanisms of angiogenesis in hepatoblastoma - Kong, Meng; Zhai, Yunpeng; Liu, Hongzhen; Zhang, Shisong; Chen, Shuai; Li, Wenfei; Ma, Xiang; Ji, Yi (Frontiers in Cell and Developmental Biology, 2025)
Hepatoblastoma (HB), the most common pediatric liver malignancy, is characterized by aggressive growth and metastasis driven by complex angiogenic mechanisms. This review elucidates the pivotal role of angiogenesis in HB progression, emphasizing metabolic reprogramming, tumor microenvironment (TME) dynamics, and oncogenic signalling pathways. The Warburg effect in HB cells fosters a hypoxic microenvironment, stabilizing hypoxia-inducible factor-1α (HIF-1α) and upregulating vascular endothelial growth factor (VEGF), which synergistically enhances angiogenesis. Key pathways such as the Wnt/β-catenin, VEGF, PI3K/AKT, and JAK2/STAT3 pathways are central to endothelial cell proliferation, migration, and vascular maturation, whereas interactions with tumor-associated macrophages (TAMs) and pericytes further remodel the TME to support neovascularization. Long noncoding RNAs and glycolytic enzymes have emerged as critical regulators of angiogenesis, linking metabolic activity with vascular expansion. Anti-angiogenic therapies, including VEGF inhibitors and metabolic pathway-targeting agents, show preclinical promise but face challenges such as resistance and off-target effects. Future directions advocate for dual-target strategies, spatial multiomics technologies to map metabolic–angiogenic crosstalk, and personalized approaches leveraging biomarkers for risk stratification. This synthesis underscores the need for interdisciplinary collaboration to translate mechanistic insights into durable therapies, ultimately improving outcomes for HB patients.